Fostering Character Education through Community-Based Socialpreneurship Initiatives among High School Students in Banda Aceh - Nizariah, Nizariah; Suhendrayatna, Suhendrayatna; Aulia, Muhammad; Sulastri, Sulastri (Pandawan, 2025)
This study explores the development of a character-building model that integrates the Merdeka Curriculum and School-Driven Program to foster religious and social care values among high school students in Banda Aceh. Using a qualitative approach, data was collected through observations, in-depth interviews, and documentation analysis, involving school principals, teachers, students, and community members from four high schools in Banda Aceh. Triangulation of sources and techniques ensured data validity. The findings show that each school employs unique character-building strategies aligned with its vision and mission. The study emphasizes the importance of proactive school leadership, teacher engagement, and community collaboration in successful character education. To address challenges such as cultural differences, student readiness, and resource limitations, the Busi (Islamic School Culture) model was developed. This model integrates religious values and social activities, enhancing students discipline, empathy, and social skills. The implementation of the Busi model led to significant improvements in students moral and social development. The study underscores the need for integrating religious and social values into the curriculum and fostering collaboration between schools, families, and communities to achieve holistic character education.